The Effect of Total Physical Response (TPR) Method and Word List for Teaching Vocabulary to Children - Fifin Yanuarita (Widya Mandala Surabaya Catholic University, 2008)
The writer conducted a study about teaching vocabulary by using the Total Physical Response method and Word List. The objective of this study is to find out whether the students taught with Total Physical Response method have obtained higher vocabulary achievement than taught with word list. The result showed that there was a significant difference between the mean scores of the two groups. Therefore, it can be concluded that the third grade students taught with Total Physical Response method got higher vocabulary achievement than those taught with Word List. In short, it can be said that teaching vocabulary using Total Physical Response method is more successful than using word list.